Common Grasses of Gorakhpur - Gupta, P. K. (Indian Forester, 1969)
The paper deals with an enumeration of the grass flora of Gorakhpur, A total number of 76 spceis and 45 genera belonging to the 3 tribes of Panicoideae and 11 tribes of Posideae are described. Of these 14 tribes, the tribe Andropogonear, Eragosteae and Paniceae dominate, having 28, 15 and 23 species respectively. Echinochloa frumentacea Link, Eragrostis paeoides P. Beauv., Eragastis termula Hochst., Setaria viridis (Linn.) P. Beauv., and Bothriachloa ischaemum (Linn.) Keng described in this paper are not listed by Raizada (1954) in his list of grasses of the Upper Gangetic Plain.